Activation of organic reactions by perchlorates - Deshpande, Suvarna S.; Kumar, Anil (Advances in Organic Synthesis, 2005)
Perchlorates have been frequently employed to promote a variety of synthetic transformations under ambient conditions. For example, the LiClO4-diethyl ether solvent medium has proven to be a powerful substitute for external high pressure for Diels-Alder reactions and other organic reactions. In this chapter are discussed several such organic transformations where perchlorates have played highly significant role in promoting their rates and yields.